Fatty Acid Desaturase Gene Variants, Cardiovascular Risk Factors, and Myocardial Infarction in the Costa Rica Study - Aslibekyan, Stella; Jensen, Majken K.; Campos, Hannia; Linkletter, Crystal D.; Loucks, Eric B.; Ordovas, Jose M.; Deka, Ranjan; Rimm, Eric B.; Baylin, Ana (Frontiers in Genetics, 2012)
Genetic variation in fatty acid desaturases (FADS) has previously been linked to long-chain polyunsaturated fatty acids (PUFAs) in adipose tissue and cardiovascular risk. The goal of our study was to test associations between six common FADS polymorphisms (rs174556, rs3834458, rs174570, rs2524299, rs174589, rs174627), adipose tissue fatty acids, intermediate cardiovascular risk factors, and nonfatal myocardial infarction (MI) in a matched population based case-control study of Costa Rican adults (n=1756). Generalized linear models and multiple conditional logistic regression models were used to assess the associations of interest. Analyses involving intermediate cardiovascular risk factors and MI were also conducted in two replication cohorts, The Nurses’ Health Study (n=1200) and The Health Professionals Follow-Up Study (n=1295). In the Costa Rica Study, genetic variation in the FADS cluster was associated with a robust linear decrease in adipose gamma-linolenic, arachidonic, and eicosapentaenoic fatty acids, and significant or borderline significant increases in the eicosadienoic, eicosatrienoic, and dihomo-gamma-linolenic fatty acids. However, the associations with adipose tissue fatty acids did not translate into changes in inflammatory biomarkers, blood lipids, or the risk of MI in the discovery or the replication cohorts. In conclusion, fatty acid desaturase polymorphisms impact long-chain PUFA biosynthesis, but their overall effect on cardiovascular health likely involves multiple pathways and merits further investigation.